AN INTEGRATED MOBILE LEARNING APPROACH: ESTABLISHING A NEW ATKP SURABAYA’S LEARNING CULTURE AND SYSTEM - Bakri, Muhammad Amin (RESULTAN : Jurnal Kajian Teknologi, 2011)
The convergence of telecommunications and information technology has accelerated the application of mobile technology in various areas of society, including the field of learning. M-learning (mobile learning) is only one kind of the application of mobile technology in education and training that is now being popularized, applied and available in the market place. As an institution that promotes modern education and training in the Ministry of TransportationRepublic of Indonesia, ATKP (Akademi Teknik dan Keselamatan Penerbangan) Surabaya anticipated the change of learning technology. To meet this challenge, ATKP hasstarted to implement m-learning and its integration with other learning system. As a result, ATKP is now able to provide the technology, establish the rules and policy, help develop human resource, as well as provide benchmarking services. Up to this date, ATKP has achieved and implemented a whole new idea in learning, especially in utilizing information and communication technology in mobile learning, as shown by their staff as well as the cadets. It is recognized that the ATKP future development is largely determined by the efforts related to the growing awareness in the academic community in optimizing new learning resources that have been constructed.